Public Employees Adherence to Life Quality Program and Nutritional Intervention - Maia de Sousa, Taciana; dos Santos Rodrigues, Ana Maria; Liberato Ferreira Campos, Bárbara Danielle; Porfírio Couto, Ana Cláudia; Ribeiro de Oliveira, Dirce (O Mundo da Saúde, 2015)
It is a non-controlled nutritional intervention study with three months length, which aimed to evaluate the adherence of public employees to life quality program and nutritional intervention. Nutritional evaluation and individualized guidelines were made and questionnaires regarding accession to the participants who left the nutritional monitoring. Began the study 52 individuals, mostly women (76,9%), with an average of 40,8 ± 8,9 years old. Any meaningful alteration was observed after nutritional intervention. The rate of abandonment to nutritional intervention 55,8% and 78,3% of them gave up the other program activities. The main reason for abandonment were dissatisfaction with the time of activities (44,4%), lack of motivation (27,8%), and health problems (22,2%). Among employees who continued the physical activity and did not returned to nutritional consultation, 60,0% reported difficulty in leaving job to attend the evaluations and 40,0% did not feel motivated to return. The low adherence to the program and nutritional intervention may have contributed to the lack of dietary and anthropometric modification. Evaluate intervention strategies becomes important to restructure the methods and increase the participation of individuals.